EXISTE DIFERENÇA ENTRE OS RETORNOS DAS EMPRESAS LISTADAS NO IBOVESPA E NOS NÍVEIS DE GOVERNANÇA CORPORATIVA? - Ribeiro, Kleber dos Santos (2011)
This research aimed to verify whether there are differences between the returns of companies listed on the BOVESPA and the level of corporate governance established by the BOVESPA in December 2000 in order to differentiate between companies that voluntarily adopt additional corporate governance practices. The main goal since the process is to improve transparency between investors and companies, thereby reducing the information asymmetry. To perform this research was first conducted a literature review on information asymmetry, transaction cost theory, agency theory and a history of corporate governance in the world and in Brazil. To check whether there are differences between the returns of the companies listed in IBOVESPA and different levels of corporate governance used the statistical model ANOVA and t test on a sample of all listed companies in IBOVESPA they had in stock 31/03/2011 negotiated between 2006 and 2010 which are the last five years of implementation of the levels of governance in Brazil. As a result it was found that firms listed on the Novo Mercado and Level 1 have higher returns than traditional listed companies in the market.